Exploring Student Perspectives on Quality Assurance in Independent Curriculum Services within Educational Institutions - Agus, Abu Hasan; Norman, Efrita; Hamid, Nur; Hasanah, Uswatun (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2023)
This study examines students' perceptions of quality assurance of independent curriculum services implemented by SMA Nurul Jadid. Using a descriptive quantitative approach. With a proportional random sampling technique, as many as 100 students. The type of data collected is quantitative, using a closed questionnaire. The questionnaire was tested for validity and reliability with a significance of 0.05 with the SPSS 16 application. A Likert scale of 1-4 was used to measure student perceptions with positive and negative categories. The following are tangible, reliability, and assurance indicators as indicators of quality assurance for the independent curriculum service. The percent interval is used as a measuring tool to determine the categories of strongly agree/very good, agree/good, disagree/good enough, and strongly disagree/strongly disagree with implementing quality assurance services for the independent curriculum. The research results prove that 58% of students perceive positively and 42% negatively. However, no students rated it as very bad at 0%; in fact, the good category was the most percentage, namely 59%, and even perfect at 7%; there were also those who rated it quite well, as much as 34%. The assessment of the most significant percentage being good is due to the socialization process evenly distributed to all components of the school; staff, teachers, students, and parents. This is done to process the quality assurance of the independent curriculum services provided by schools to run effectively and efficiently.